Hydrogen bonding assissted supramolecular metal catalysis - Mote, Nilesh R.; Chikkali, Samir H. (Chemistry - an Asian Journal, 2018)
The process of catalyst screening and discovery still largely relies on traditional ligand-design approaches, which suffer from complex synthetic requirements and offer limited structural diversity. On the contrary, supramolecular chemistry offers the potential to harness multiple weak secondary interactions to deliver self-assembled catalysts with diverse structures or to orient substrates to achieve enzyme-like activity and selectivity. Herein, the application of hydrogen-bonding (H-bonding) interactions as a construction element and directing group in "supramolecular transition-metal catalysis" is critically reviewed and the current state-of-the-art in the field is presented. H-bonding interactions empower structurally simple ligands to deliver complex self-assembled catalysts, which have been found to catalyze a gamut of organic transformations, including hydroformylation, hydrogenation, and allylation reactions. As we will discuss, on many occasions, these supramolecular catalysts outperform their analogous covalently linked catalytic systems. The potential of H-bonding interactions as directing groups has recently been recognized by the scientific community and this Focus Review presents the role of hydrogen-bonding interactions in directing substrates to obtain excellent selectivities and activities in a range of catalytic transformations